Influencer Marketing Impact on Consumer Trust in Cross-Border E-Commerce Transactions - Scherly Hansopaheluwakan; Arif Budiarto; Ida Nuryana; Neneng Nurbaeti Amien; Fitria Virgantari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explores how influencer marketing influences consumer trust in cross-border e-commerce, an emerging focus in digital marketing. Using a qualitative approach through literature review and library research, it investigates the connection between influencer marketing and consumer behaviour in international markets. The primary focus is on how influencer credibility, engagement, and cultural adaptation influence consumer trust when purchasing from international brands. The review reveals that influencer marketing plays a critical role in reducing perceived risks in cross-border transactions by providing social proof and authenticity, particularly when influencers align their content with local cultural norms. The findings indicate that both macro and micro-influencers play an important role, though their effectiveness depends on the target market and campaign objectives. Micro-influencers tend to perform better in niche markets because of their strong engagement and authenticity, while macro-influencers offer wider reach and authority, making them valuable for large-scale cross-border campaigns. This highlights the need to select appropriate influencers and tailor strategies to cultural contexts for successful international marketing efforts.